Teacher needs for implementation of special needs early childhood intervention program - Abdullah, Nur Aishah; Abdullah, Nur Ain Elzira (Jurnal Pendidikan Bitara UPSI, 2019)
Special needs pupils are the human capital that needs to be given attention so that they are able to live independently and improve their self-reliance towards a successful career while contributing to the nation's development. The 21st Century skills are aimed at producing students who can compete globally. Therefore, this study was conducted to identify teachers' need for early intervention programs in special education preschools. The design of this study used a quantitative approach through the survey method using questionnaire instruments to obtain data. A total of 161 special education preschool teachers were selected through simple random sampling to answer the questionnaire. Aspects of teacher needs include training, collaboration, infrastructure and monitoring. While the implementation of early intervention involves aspects of planning and implementation. Instructors' needs were modified from the Malaysian Teacher's Standard instrument while the instrumentation of the initial intervention program was developed by the researchers based on the literature review appropriate to the scope of the study. Overall, the level of teacher needs in terms of training, collaboration, infrastructure, monitoring and teacher perspective in terms of planning and implementation are high. Kruskal Wallis analysis showed that there was a significant difference in teacher needs based on academic approval whereas in the overall MANOVA analysis, there were differences in teacher needs based on location. The implications of this study are that in order to achieve effective early intervention quality, the needs of teachers in terms of training, collaboration, infrastructure and monitoring should be given due attention.